Incorporating a percutaneous ventricular assist device into an existing cardiogenic shock programme - early experience from an asian heart center - ZY, Ng; FE, Tulod; Hwei Sung, Ling; R, Cherian; YC, Lim; RCC, wong; AA, Ambhore; SL, Lim; Q, Qian; JA, Sule; G, Maclaren; K, Ramanathan; et al. (Wiley, 2024)
Background: The use of mechanical circulatory support in acute heart failure complicated by cardiogenic shock (CS) is increasing worldwide. We report our early experience with a percutaneous left ventricular assist device (pVAD) in the treatment of CS at an Asian tertiary heart centre.